Huling araw a comic on the influence of neoliberalism and the privatization of public land transport to the public utility vehicle modernization plan - Valerio, Gabriel Ker F.
The Public Utility Modernization Plan is a flagship program of the Duterte administration. Public land transport in the Philippines has been found wanting especially here in Metro Manila where the density of people is the highest in the whole country. With the analysis of literature this research attributes the decline in public land transport to privatization, which is the transfer of state services into private hands. This transfer commodifies public service and alters the motivations of public service into pursuit of profit. Privatization stems from Neoliberalism, which is an economic model and ideology that believes in the market and its ability to advance society and liberate the people. The ideology applies market principles such as competition not only in the economy but in all aspects of life. This application of market values has halted the advancement of public transport in the Philippines as profit becomes the priority rather than the people, issues of equity and accessibility remain unanswered as long as profit is maintained. The PUVMP is a manifestation of the neoliberal application of market principles into public service.